Gut mycobiota dysbiosis and systemic immune dysfunction in Chinese schizophrenia patients with metabolic syndrome - Ling, Zongxin; Cheng, Yiwen; Lan, Zhiyong; Liu, Xia; Zhu, Zhangcheng; Ding, Wenwen; Xu, Xiaocui; Yu, Pian; Xu, Xiaoxun; Shao, Li; Song, Qinghai; Liao, Rongxian (Frontiers in Immunology, 2025)
While bacterial dysbiosis has been extensively studied in schizophrenia with metabolic syndrome (SZ-MetS), the role of gut mycobiota in this comorbidity remains unclear. This study represents the first comprehensive investigation of fungal communities in SZ-MetS patients (n=109) versus healthy controls (HCs, n=101) using ITS1 sequencing and multi-parameter immune profiling. Although global mycobiota structure showed no significant differences, compositional analyses revealed profound taxonomic shifts: pathobionts (Trichosporon asahii, Candida albicans, Lodderomyces elongisporus) were enriched, while putative beneficial species (Saccharomyces cerevisiae, Pleurotus ostreatus) were reduced in patients. Enterotyping identified two mycobiota clusters (Candida-dominant vs Aspergillus-dominant), though their distribution was similar between groups. Notably, machine learning revealed a six-species fungal signature with strong diagnostic potential (AUC = 0.86). Species-specific immune correlations were also observed: inflammatory cytokines such as IL-6 and MIP-1α were positively associated with Ustilago esculenta and Trichosporon asahii, but negatively correlated with Saccharomyces cerevisiae. Furthermore, fungal abundances were differentially correlated with metabolic and psychiatric parameters, with Lodderomyces linked to elevated triglycerides and S. cerevisiae associated with reduced symptom severity. These findings reveal that while overall fungal community structure is preserved, SZ-MetS exhibits distinct mycobiota alterations that interact with host immunity and clinical manifestations, suggesting fungi may contribute to the SZ-MetS vicious cycle through taxon-specific mechanisms.